Specificity and Effectiveness of the Programs for the Development of Managerial Competencies of Personnel Reserve - V. D. Kolychev; I. O. Belkin; R. S. Udovidchenko (Высшее образование в России)
The article analyses the experience of the National Research Nuclear University «MEPhI» (hereinafter the University) in the field of formation of managerial competences of the personnel reserve. The authors dwell on the features of implementation of training and developing programs in the field of additional professional education, discuss the issues of the efficiency and effectiveness of realization of training actions. The model of formation and development of the personnel reserve of the University is oriented primarily on solving the problems of increasing competitiveness by enforcing the competencies of high-potential employees in the following key spheres: performance management, goal-setting, motivation, effective communication, time management, planning, organization and control. The model is based on the best practices of domestic and foreign high-tech corporations and educational organizations, primarily using the experience of Rosatom State Atomiс Energy Corporation. The personnel reserve is considered as a competitive advantage in improving the efficiency and effectiveness of activities within the framework of strategic development and implementation of target promising high-tech and knowledge-intensive projects and programs.